A comparative analysis of the effectiveness of the Budapest Convention and the UN cybercrime treaty – a human rights dilemma? - Kissoon, Christina Amanda (Riga Graduate School of Law, 2024)
The bachelor thesis “A Comparative Analysis of the Effectiveness of The Budapest Convention and The UN Cybercrime Treaty – A Human Rights Dilemma?” provides an in-depth comparative analysis of both treaties. The thesis establishes effectiveness criteria to conclude to what extent each treaty is effective. To determine the effectiveness of both treaties the following criteria were established and analysed: human rights, enforcement mechanism and international cooperation. The thesis also puts a large emphasis on the enforcement procedure provisions within The Budapest Convention and The UN Cybercrime Treaty and the potential impact of these provisions on fundamental human rights violations.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Cybercrime; The Budapest Convention; The UN Cybercrime Treaty; Research Subject Categories::LAW/JURISPRUDENCE::Criminal law; Human rights